Anthropology as memory : Elias Canetti's and Franz Baermann Steiner's responses to the Shoah - Mack, Michael, 1969-2020 (Conditio Judaica ;, 2001)
Whereas many other post-Holocaust Jewish thinkers - including Derrida - have concentrated on a refusal of totality and celebration of 'otherness', the poet and intellectual Franz Baermann Steiner (1909-1952) combines this emphasis with an equal stress on the 'need' for certain collectively acknowledged limits. Next to the wider significance of this book for discussions of Holocaust studies in relation to current theoretical and social issues, it will also offer a new interpretation of Elias Canetti's work. This is the first detailed examination of Steiner's anthropology and philosophy and its.